A multi-platform validation of biomass burning emissions: Integrating ground, airborne, and satellite data to quantify regional haze health impacts in Thailand - Ratchaphon Samphutthanont; James H. Crawford; Ittipol Pawarmart; Armin Wisthaler; Stefan J. Swift; Felix Piel; Wojciech Wojnowski; Jose L. Jimenez; Pedro Campuzano-Jost; Seonsik Yun; Guy Symonds; Douglas A. Day; et al. (Environmental Pollution, 2026)

Impact of body mass index on blood pressure and cardiovascular adaptation to isometric exercise training - Harry T. Swift; Christopher K. Farmer; Jonathan D. Wiles (European Journal of Applied Physiology, 2026)
Objectives Obesity is characterised by excess adipose tissue, which impairs vascular function and blood pressure (BP) regulation. However, it remains unclear whether adiposity influences the BP-lowering response to isometric exercise training (IET). This randomised-controlled trial explored the impact of body mass index on BP and cardiovascular adaptation following IET. Methods 80 participants with normal to high-normal systolic BP (range 120-140 mmHg) were recruited for the study. Participants were randomised into two BMI groups: normal BMI (18.5–24.9 kg/m²; n=40) and high BMI (25-34.9 kg/m²; n=40) and then either performed home-based lower-body IET, 3 times per week, for 4 weeks (each session comprised 4 x 2-minute bouts), or were allocated to the control group. Cardiovascular variables, including BP, total peripheral resistance (TPR), and heart rate variability (HRV), were measured at rest pre- and post-intervention. Results Overall, there were significant reductions in systolic BP, diastolic BP and mean arterial pressure (MAP) in the IET group compared to control. However, the normal-BMI group had significantly greater reductions in diastolic BP (– 8.5 [– 11.8, – 5.3] mmHg) and MAP (– 9.2 [– 11.9, – 6.6] mmHg) compared to the high-BMI group (dBP: – 2.6 [– 6.2, 1.1]; MAP: -4.7 [– 7.6, – 1.8]). Although TPR was significantly greater in the high-BMI group at week 4 (p=0.022), it was also elevated at baseline, and change-score analyses revealed no significant between-group difference in the magnitude of TPR reduction (Δ p=0.964). Conclusion These findings indicate that BMI may modulate the BP-lowering response to IET, suggesting that individuals with higher BMI may require adjunctive or prolonged interventions to optimise BP reduction.

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Perinatal oxycodone exposure causes long-term sex-dependent changes in weight trajectory and sensory processing in adult mice - Elena Minakova; Marwa O. Mikati; Manish K. Madasu; Sineadh M. Conway; Justin W. Baldwin; Raylynn G. Swift; Katherine B. McCullough; Joseph D. Dougherty; Susan E. Maloney; Ream Al-Hasani (Psychopharmacology, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Acute cardiac autonomic and haemodynamic responses to leg and arm isometric exercise - Harry T. Swift; Jamie M. O’Driscoll; Damian D. Coleman; Anthony De Caux; Jonathan D. Wiles (European Journal of Applied Physiology, 2022)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Breeding habitat of a declining shorebird in a changing environment - Rose J. Swift; Amanda D. Rodewald; Nathan R. Senner (Polar Biology, 2017)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

A novel molecular mechanism to explain biotin-unresponsive holocarboxylase synthetase deficiency - Lungisa Mayende; Rachel D. Swift; Lisa M. Bailey; Tatiana P. Soares da Costa; John C. Wallace; Grant W. Booker; Steven W. Polyak (Journal of Molecular Medicine, 2012)

Modeling Jack Pine ( Pinus banksiana ) Foliage Density Distribution - Robert Schneider; Mathieu Fortin; Frank Berninger; Chhun-Huor Ung; D. Edwin Swift; S.Y. Zhang (Forest Science, 2011)
The vertical distribution of foliage biomass is important because it is associated with photosynthesis and is closely related to some wood quality attributes such as branch diameter and sapwood content. In this article we propose a model to predict foliage biomass distribution within the crown for jack pine trees in Eastern Canada. This model has two parts. The first one distinguishes the proportion of nodal (formed at the end of each yearly shoot) and internodal (formed during the growing season) foliage biomass. The second part of the model predicts the distribution of the biomass depending on the type of foliage (nodal or internodal). This second part is based on a two-parameter beta cumulative distribution function (cdf). The parameterization of this cdf was performed using a mixed-effects nonlinear regression. The proportion of foliage biomass found in the nodal whorls is proportional to dbh and age and inversely proportional to total height. The distribution of the foliage biomass in the nodal whorls is dependent only on tree-level variables whereas the internodal foliage biomass is influenced by both tree- and stand-level variables. The internodal foliage biomass maximum is closer to the crown base than that of nodal foliage biomass. Decomposing the distribution into whorl types leads to a better description of crown characteristics.

Rangewide microsatellite phylogeography of the endangered tidewater goby, Eucyclogobius newberryi (Teleostei: Gobiidae), a genetically subdivided coastal fish with limited marine dispersal - Dent A. Earl; Kristina D. Louie; Carolyne Bardeleben; Camm C. Swift; David K. Jacobs (Conservation Genetics, 2010)

Male-Produced Aggregation Pheromone of the Cerambycid Beetle Rosalia funebris - Ann M. Ray; Jocelyn G. Millar; J. Steven McElfresh; Ian P. Swift; James D. Barbour; Lawrence M. Hanks (Journal of Chemical Ecology, 2009)

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Water clarity modeling in Lake Tahoe: Linking suspended matter characteristics to Secchi depth - Theodore J. Swift; Joaquim Perez-Losada; S. Geoffrey Schladow; John E. Reuter; Alan D. Jassby; Charles R. Goldman (Aquatic Sciences, 2006)

Underground excavations in rock salt - G. M. Swift; D. J. Reddish (Geotechnical and Geological Engineering, 2005)

Combining carbon sequestration objectives with timber management planning - Fan-Rui Meng; Charles P.-A. Bourque; Steven P. Oldford; D. Edwin Swift; Helen C. Smith (Mitigation and Adaptation Strategies for Global Change, 2003)

Stability problems associated with an abandoned ironstone mine - Swift G.; Reddish D. (Bulletin of Engineering Geology and the Environment, 2002)

Comparative phylogeography of sympatric sister species, Clevelandia ios and Eucyclogobius newberryi (Teleostei, Gobiidae), across the California Transition Zone - M. N Dawson; K. D. Louie; M. Barlow; D. K. Jacobs; C. C. Swift (Molecular Ecology, 2002)
It is paradigmatic in marine species that greater dispersal ability often, but not always, results in greater gene flow and less population structure. Some of the exceptions may be attributable to studies confounded by comparison of species with dissimilar evolutionary histories, i.e. co‐occurring species that are not closely related or species that are closely related but allopatric. Investigation of sympatric sister species, in contrast, should allow differences in phylogeographic structure to be attributed reliably to recently derived differences in dispersal ability. Here, using mitochondrial DNA control region sequence, we first confirm that Clevelandia ios and Eucyclogobius newberryi are sympatric sister taxa, then demonstrate considerably shallower phylogeographic structure in C. ios than in E. newberryi . This shallower phylogeographic structure is consistent with the higher dispersal ability of C. ios , which most likely results from the interaction of habitat and life‐history differences between the species. We suggest that the paradigm will be investigated most rigorously by similar studies of other sympatric sister species, appended by thorough ecological studies, and by extending this sister‐taxon approach to comparative phylogeographic studies of monophyletic clades of sympatric species.

Effect of luminance level on electro-encephalogram alpha-wave synchronisation - A. M. Maher; L. Kirkup; P. Swift; D. Martin; A. Searle; Y. Tran; A. Craig (Medical & Biological Engineering & Computing, 2001)

Extirpation and Recolonization in a Metapopulation of an Endangered Fish, the Tidewater Goby - Kevin D. Lafferty; Cam C. Swift; Richard F. Ambrose (Conservation Biology, 1999)
The tidewater goby ( Eucyclogobius newberryi ), an endangered species in the United States, occurs in a series of isolated coastal wetlands in California. Using historical presence‐absence data and our own surveys, we estimated annual rates of extirpation and recolonization for several populations of the goby in southern California. As predicted, large wetlands had lower rates of extirpation than small wetlands. There was a negative but statistically nonsignificant correlation between recolonization rate and distance to the nearest northerly source population. Populations at small sites were sensitive to drought, presumably because droughts can eliminate suitable habitat at small wetlands. Populations in small wetlands have declined over time, even after accounting for variation in stream flow, supporting the species' endangered status. Our study emphasizes the need to understand metapopulation dynamics for conserving species where the unit of conservation is a local population. It is also emphasizes the importance of not treating metapopulations as identical units. Finally, our results provide a means for describing the decline of a species that is complex in time and space and provide insight into how to target protection measures among metapopulations.

Alley cropping of maize with calliandra and leucaena in the subhumid highlands of Kenya: Part 2. Biomass decomposition, N mineralization, and N uptake by maize - D. N. Mugendi; P. K. R. Nair; J. N. Mugwe; M. K. O'Neill; M. J. Swift; P. Woomer (Agroforestry Systems, 1999)

Effects of naltrexone with nicotine replacement on smoking cue reactivity: preliminary results - K. E. Hutchison; Peter M. Monti; Damaris J. Rohsenow; Robert M. Swift; Suzanne M. Colby; Maryann Gnys; Raymond S. Niaura; Alan D. Sirota (Psychopharmacology, 1999)

Psychomotor performance: investigating the dose-response relationship for caffeine and theophylline in elderly volunteers - C. A. Bryant; A. Farmer; B. Tiplady; J. Keating; R. Sherwood; C. G. Swift; S. H. D. Jackson (European Journal of Clinical Pharmacology, 1998)

Potentials of Millettia thonningii and Pterocarpus santalinoides for alley cropping in humid lowlands of West Africa - E. A. Egbe; D. O. Ladipo; L. C. Nwoboshi; M. J. Swift (Agroforestry Systems, 1998)